Contrafação monetária de cédulas brasileiras - Tatum, Carlos Tadeu Santana (2015)
The developed research sought to achieve an interdisciplinary approach to counterfeiting of the Brazilian Real ballots, identifying its possible innovations and socio-economic impacts, aiming in their considerations propose possible solutions to minimize the possible losses arising from the issue to the Company. The method was characterized by case study applied to Real ballots of the Brazilian currency, using bibliographic and documentary resources complemented by field studies through an interdisciplinary approach involving disciplines such as history, law, economics and Technological Innovation. For elements of history, there was a brief overview of the emergence of money in Brazil and the various denominations modified until the appearance of the second family of the real, still pointing the first counterfeit registration in Brazil, as the law of the aspects was mainly aimed the elements that make up the legal framework protecting the rights related to intellectual property. With regard to the economy was still drawn a macroeconomic analysis of counterfeit depending on income and the number of inhabitants. In aspects of technological innovation were accounted for the various innovations occurring in the manufacture of Real ballots since its existence to the present day. The results showed by basic principles of Applied Statistics that 100 people at least 4 possibly handled a false ballot and to minimize the increasing falsification of ballots, one should invest in technological safety innovations and conscious orientation to society.